Making sense of American liberalism - Bell, Jonathan, 1976-; Stanley, Timothy (University of Illinois Press, 2012)
This collection of thoughtful and timely essays offers refreshing and intelligent new perspectives on postwar American liberalism. Sophisticated yet accessible, 'Making Sense of American Liberalism' challenges popular myths about liberalism in the United States.